2021
DOI: 10.1016/j.dsx.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Using structural equation modeling to predict Indian people's attitudes and intentions towards COVID-19 vaccination

Abstract: Background and aim Understanding people's attitudes towards Covid-19 vaccination is crucial to the successful implementation of a vaccination program. Hence this research study seeks to identify critical factors influencing Indian people's attitudes and intentions to take up Covid-19 vaccinations. Methods An online questionnaire was administered to a sample (n = 254) drawn from Indian population, to assess the impact of perceived benefits, risk perceptions, social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(106 citation statements)
references
References 33 publications
9
78
1
Order By: Relevance
“…Studies show that those who believe they are at greater risk or risk of infection are more likely to receive vaccines [55][56][57][58]. A survey of India's intention to vaccinate COVID-19 found that risk disclosure was not significantly associated with India's intention to become vaccinated [59], where non-vaccination risks are higher than the side effects of the vaccine itself, resulting in inconsistent results with our findings.…”
Section: Effect Of Risk Disclosure On Vaccination Intentioncontrasting
confidence: 89%
“…Studies show that those who believe they are at greater risk or risk of infection are more likely to receive vaccines [55][56][57][58]. A survey of India's intention to vaccinate COVID-19 found that risk disclosure was not significantly associated with India's intention to become vaccinated [59], where non-vaccination risks are higher than the side effects of the vaccine itself, resulting in inconsistent results with our findings.…”
Section: Effect Of Risk Disclosure On Vaccination Intentioncontrasting
confidence: 89%
“…Impact: A person’s awareness and knowledge about the benefits of the action to undertake can ensure a successful launch of any new initiative. If people feel that their actions would contribute to the general welfare of the society, they are more likely to adopt a change in behavior [14] , [25] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knowledge: Knowledge about a new initiative or goal increases a person’s confidence and self-esteem, which further increases their trust in the initiative and benefits the organization. Accordingly, when people have more knowledge about the vaccine, the different types of vaccines available, and their benefits and their side-effects, they are more likely to make an informed choice [14] , [27] .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting protective behaviors in response to infectious respiratory illnesses such as hand cleanliness, social distance, and mask-wearing can significantly influence the course of a pandemic. PMT [30,31] and TPB [32,33] provide valuable frameworks for analyzing behavioral choices during such outbreaks. Individuals are primarily motivated to engage in protected activity when confronted with a frightening situation.…”
Section: Theoretical Foundationmentioning
confidence: 99%